Meningkatkan Motivasi Belajar Melalui Problem Based Learning Pada Materi Perkelahian Pelajar, Narkoba Dan Khomar Kelas Xi Akl Smk Negeri 3 Seluma - Hadikisno Hadikisno (Universitas Dehasen Bengkulu, 2024)
This study aims to improve student learning outcomes on the topics of fighting, drugs, and khamr at SMK Negeri 3 Seluma by applying the Problem-Based Learning (PBL) method. PBL was chosen for its ability to encourage active student engagement and the application of knowledge in real-life contexts. The research uses a classroom action research design involving two cycles, with each cycle consisting of planning, implementation, observation, and reflection.The subjects of the study are tenth-grade students at SMK Negeri 3 Seluma, with a focus on teaching materials related to fighting, drugs, and khamr. Data were collected through observations, interviews, and pre- and post-implementation learning tests. The results indicate that the implementation of the PBL method significantly improved students' understanding of the taught material. Students showed improvements in their ability to analyze real-life cases, make better decisions, and increase their awareness of the impacts of fighting, drugs, and khamr.Based on these findings, it can be concluded that the Problem-Based Learning method is effective in enhancing student learning outcomes on social and health-related topics. The study recommends a broader application of the PBL method across various teaching materials to improve students' critical thinking skills and awareness in the context of health and social education.